Lenguas y dialectos pano del Purús: una aproximación filogenética - Zariquiey, Roberto (2017)
The present paper aims to provide a classification of the Panoan linguistic varieties spoken in the province of Purus (Ucayali, Peru). The data covers lexical information coming from nine Panoan linguistic varieties of the Purus province, as well as grammatical information taken from eight of them. The data have been analyzed using phylogenetic methods and show the need of including all these languages in a single Panoan subgroup. The results, however, show inconsistent trends between the lexical and the grammatical data: lexical data suggest the existence of three well-defined linguistic units, while the grammatical data point towards the existence of four. This fact opens interesting questions regarding the so-called Yaminawadialectal continuum. Finally, this paper discusses the position of Iskonawa (an obsolescent Panoan language) in relation to the languages of Purus. The data shows that Iskonawa is closely-related to the languages of the Purus region.